ANALISIS PENGARUH ETIKA DAN PERILAKU AUDITOR TERHADAP PENCEGAHAN FRAUD PADA INSPEKTORAT KABUPATEN BANTAENG - Nur Arini Susanti; Gunawan Gunawan; Aulia Afrianti (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2024)
The purpose of this study is to determine how influential the Auditor's Ethics and Behavior are to Fraud Prevention in the Bantaeng Regency Inspectorate. The research design used a quantitative research approach to examine the ethics and behavior of an individual in a group with a multiple regression analysis method with the help of the SPSS 25 application. In sampling, all populations were sampled as many as 38 people. The findings of this study indicate 1) auditor ethics do not affect fraud prevention in the Bantaeng Regency Inspectorate, 2) auditor behavior has a positive and significant effect on fraud prevention in the Bantaeng Regency Inspectorate 3) auditor ethics and auditor behavior simultaneously have a positive and significant effect on fraud prevention in the Bantaeng Regency Inspectorate